A clinical study on maternal and fetal outcome in pregnancy with oligohydromnios - Gupta, Chetan Prakash; Choudhary, Jaya; Chahar, Deepika; Yadav, Sapna Kumari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Oligohydramnios is associated with various maternal and fetal complication. It’s correlated fetal complications like FGR, increased risk of meconium aspiration syndrome, Birth asphyxia, low APGAR scores and increased congenital abnormalities in fetus. It’s also associated with maternal morbidities in view of operative interventions for delivery. To study effect of oligohydramnios in mother in form of, operative delivery and progress of labour. To study effect of oligohydramnios in fetus in form of fetal compromise i.e. FGR, fetal distress, altered APGAR score, need for NICU admission. congenital anomaly and perinatal death. Methods: 50 patients with ≥ 28 weeks POG with oligohydramnios, confirmed by ultrasonographic measurement of AFI using four quadrant technique; were selected randomly after fulfilling inclusion and exclusion criteria. Results: Incidence of oligohydramnios were more found in primigravida (56%) in present study. Most common cause of oligohydramnios was idiopathic (62%) followed by PIH (20%). Most common cause of caesarean was fetal distress (23%) either due to cord compression or FGR. oligohydramnios was related to higher rate of Fetal Growth restriction and NICU admission (24%). Conclusions: Oligohydramnios is very common encounter during pregnancy, Because of its frequent occurrence; it demands intensive fetal monitoring and systemic approach to antepartum and intrapartum fetal surveillance. There is increased risk of intrapartum complication, perinatal morbidity, perinatal mortality; thus, the rate of caesarean increasing day by day.one should always know the fine line between vaginal delivery and caesarean section; move ahead with best option without hampering fetal wellbeing and avoid unnecessary operative morbidity.